ПРО ДЕЯКІ ОСОБЛИВОСТІ ПОБУДОВИ ІНТЕЛЕКТУАЛЬНИХ БАГАТОРІВНЕВИХ СИСТЕМ ТЕХНІЧНОЇ ДІАГНОСТИКИ ЕЛЕКТРОЕНЕРГЕТИЧНИХ ОБ’ЄКТІВ - Мислович, М.В.; Сисак, Р.М. (Інститут електродинаміки НАН України, Київ, 2015)
The main goal of the paper is development of structure of intelligent distributed multi-level system for technical diagnostics of power electrical equipment. The discussed system implements the following general principles: distribution of computational resources between different levels which is needed to support required periodicity of measurements and signal processing; structuring of the diagnostic information on hierarchical principle; classification of the diagnostic information by severity level for the optimization of information exchange. This structure of the developed system complies with the basic requirements of the Smart Grid concept: bi-directional exchange of information between system elements, and decentralization of computing resources. One possible implementation of the system is discussed, which consists of 4 hierarchical levels typical to an average power plant. The structure represents central diagnostic system, a number of local diagnostic systems and intelligent measuring devices. The paper details the logic of data exchange between different hierarchical levels and their main functions. References 9, table 1, figures 4.